Effect of Low-Frequency Repetitive Transcranial Magnetic Stimulation on Executive Function and Its Neural Mechanism: An Event-Related Potential Study - Liu, Sishi; Wang, Xianglong; Ma, Junqin; Wang, Kangling; Wang, Zhengtao; Li, Jie; Chen, Jiali; Zhan, Hongrui; Wu, Wen (Frontiers in Neuroscience, 2021)
Objective: Executive function refers to the conscious control of thinking and behavior in psychological process. Executive dysfunction widely exists in a variety of neuropsychiatric diseases, and is closely related to the decline of daily living ability and function. This study intends to explore the effect of low-frequency repetitive transcranial magnetic stimulation (rTMS) on executive function and its neural mechanism by using event-related potential (ERP), so as to provide basis for further study on the relationship between cerebral cortex and executive function. Methods: Task switching paradigm was used to study the cognitive flexibility in executive function. Thirty-one healthy subjects were randomly assigned to receive rTMS stimulations (1 Hz rTMS or sham rTMS) to the left dorsolateral prefrontal cortex (DLPFC) twice. The switching task and the electroencephalography EEG recordings were performed before (pre-rTMS/pre-sham rTMS) and immediately after the end of the rTMS application (post-rTMS/post-sham rTMS). Results: The analysis of RTs showed that the main effects of switching and time were statistically significant. Further analysis revealed that the RT of rTMS stimulation was longer than sham rTMS at post-stimulation. ERP analysis showed that there was a significant switching effect in frontal and central scalp location, and the P2 amplitude in switch trials was greater than that in non-switch trials. At post-stimulation, the N2 amplitude of rTMS is more negative than that of sham rTMS at non-switch trials, whereas no such difference was found at switch trials. The P3 amplitude and LPC amplitude are significantly reduced by rTMS at post-stimulation. Conclusion: Low-frequency rTMS of the left DLPFC can cause decline of cognitive flexibility in executive function, resulting in the change of N2 amplitude and the decrease of P3 and LPC components during task switching, which is of positive significance for the evaluation and treatment of executive function.